Wave numerical model of swell and sea at Rote strait - Fuddoly Fuddoly; Dyah Iriani Widyastuti; Satria Damarnegara (Institut Teknologi Sepuluh Nopember, 2020)
A spectral wave numerical simulation based on SWAN is used to model 10 years wave climate at Rote Strait, Nusa Tenggara Timur province. ERA5 reanalysis data of total wave and wind is used for model forcing. Simulation results show waves direction in Rote strait are coming from southeast and southwest. Waves direction at nearshore of southeast Timor island coast are coming from southeast because of refraction and diffraction. Waves height over 0.8 m occurs in 320 days in one year. 50 years wave return period calculated at 2.68 m height.